Unilateral upper limb chorea associated with hyperthyroidism: A case report and literature review - Chen, Wei; Wu, Bin; An, Hongna; Zheng, Kaiying; Zhai, Daming; Zang, Jiahua; Wu, Xiaobing (Frontiers in Neurology, 2022)
Chorea, a hyperkinetic syndrome, is generally reported in patients with Huntington's disease (HD), hyperglycemia, and other diseases but occasionally occurs in patients with Grave's disease. Here, we report a 44-year-old woman presenting with a 1-year history of involuntary movements with a known history of primary hyperthyroidism. Physical examination revealed the continuous, rapid, irregular, and spontaneous choreic movement of her right arm. Laboratory investigations demonstrated increased triiodothyronine (T3) and free thyroxine (FT4) and suppressed thyroid-stimulating hormone (TSH) levels. An electroencephalogram and brain magnetic resonance imaging were normal. After antithyroid treatment, the patient achieved complete remission. Our case indicated that hemichorea might initially manifest hyperthyroidism. Therefore, thyroid function tests should be routinely performed in patients with chorea.